Obesity paradox in 12, 381 patients undergoing transfemoral transcatheter aortic valve implantation: from the CENTER-collaboration. (25th November 2020) - Van Nieuwkerk, A; Santos, R.B; Regueiro, A; Tchetche, D; Barbanti, M; D'Onofrio, A; Ribichini, F; Ten, F; Tarasoutchi, F; Orvin, K; Pagnesi, M; Ghattas, A; et al.
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is a well-established treatment for symptomatic aortic valve stenosis. The majority of patients treated are overweight or obese. Obesity has traditionally been linked to reduced survival and worse cardiovascular outcomes. However, an "obesity paradox" has been described in some diseases, with improved survival of obese patients after invasive and surgical procedures. Methods: The CENTER-collaboration included data from 10 registries or clinical trials of patients undergoing transfemoral TAVI from 2007 to 2018. Patients were divided in four groups according to body mass index (BMI): underweight: BMI <18.5 kg/m 2, normal weight: BMI 18.5 to 24.9 kg/m 2, overweight: BMI 25 to 29.9 kg/m 2, and obese: BMI ≥30 kg/m 2 . The primary endpoints of this analysis were differences in 30-day all-cause mortality and stroke after TAVI. Results: Of the 12, 381 patients analysed, 2% (n=205) were underweight, 29% (n=3552) had normal weight, 44% (n=5460) were overweight and 25% (n=3140) obese. Older patients had lower BMI (median of 84 years for underweight and 81 years for obese patients, p<0.001). Cardiovascular risk factors such as hypertension, diabetes mellitus and dyslipidaemia increased progressively with increase of BMI category. As to clinical outcomes, there were no differences for stroke rates across BMI groups. In-hospital mortality was highest in patients who were underweight, namely 8.4%, compared to normal weight, overweight and obese patients (6.2%, 4.3% and 4.6% respectively, p<0.001) as was 30-day mortality (9.8% compared to 6.9%, 5.3% and 5.2% respectively, p=0.001). On the other hand, extremely obese patients (BMI ≥40.0 kg/m 2 ) also had worse prognosis, with a 30-day mortality of 7.6%. Conclusions: In this global analysis of more than 12 000 patients undergoing transfemoral TAVI, overweight and obese patients had better in-hospital and 30-day survival than normal weight patients, confirming the obesity paradox. There was an inverted J-shaped relationship of body mass index with prognosis, with higher mortality rates for underweight and extremely obese patients. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Dutch Heart Foundation; Netherlands Organisation for Health Research and Development